Treinamento docente para aplicação de Análise Funcional Baseada em Tentativas na avaliação de comportamentos inadequados - Ferrari, Isadora Peresi (Universidade Federal de São Carlos, 2016)
Trial-based Functional Analysis is an adapted procedure from traditional Functional Analysis methodology to be used among classroom activities. The idea is to investigate problem behaviours’ function by experimentally arranging its antecedent and consequent events. Such arrangements verify if problem behaviour is maintained by positive reinforcement in form of attention or access to favourite objects, negative reinforcement through escaping from academic demands, or automatic reinforcement by self-stimulation. The present study tried to evaluate the effects of a Trial-based Functional Analysis Training Program for one teacher over her abilities to assess problem behavior. To do so, a female Special Educator was trained to conduct Trial-based FA on a female student referred for problem behaviour. The procedures took place in five phases: Initial evaluation, Pre-training, Baseline, Extended Training and Post-training. The Experimental Conditions conducted in this study during Baseline were Divided Attention, Mand and Demand. During Post-training only Mand and Demand Conditions were kept. The Inter Observer Agreement was 90%. The Training Program effects were observed by calculating and comparing procedural fidelity while the teacher was conducting the Trial-based FA at Baseline and Post-training phases. The overall results indicate that the Extended Training helped to improve teachers’ repertoire to conduct Trial-based FA in 17.9%. Looking specifically at the trials in which problem behaviour occurred, the improvement was 24.6%. This study was a first attempt to train teachers to use such applied methodology in Brazilian territory.
Teacher’s Trial-based Functional Analysis training for inadequate behaviour assessment
Keywords: Análise funcional baseada em tentativas; Educação especial; Sala de recursos; Treinamento docente; Problema de comportamento; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA COGNITIVA